Дослідження антимікробної активності цитратів срібла та міді з метою розробки фармацевтичних препаратів - Полова, Ж. М.; Полова, Ж. Н.; Polova, Zh. N. (Запорізький державний медичний університет, 2016)
Швидке формування стійкості мікроорганізмів до антибіотиків спричиняє необхідність пошуку нових, альтернативних антимікробних лікарських засобів. З метою фармацевтичної розробки препаратів вивчили антимікробну активність різних концентрацій розчинів цитрату срібла та міді стандартним методом серійних розведень на тест-штамах мікроорганізмів. Найбільш чутливим до розчину цитрату срібла виявився штам Escherichia coli ATCC 25922 (F-50) та Pseudomonas aeruginosae АТСС 9027 при концентрації срібла у розчині 10 мкг/мл. Чутливість Staphylococcus aureus 6538 Р проявилась у концентрації срібла 25 мкг/мл. Одержані під час експерименту дані вказують на те, що мінімальна інгібуюча концентрація цитрату срібла (вміст срібла 500 мкг/мл) щодо тест-штаму Staphylococcus aureus 6538 Р становить 20 мкг/мл; щодо Escherichia coli ATCC 25922 – 6,7 мкг/мл, а до Pseudomonas aeruginosae АТСС 9027 – 10 мкг/мл відповідно. Staphylococcus aureus є чутливим до розчину срібла та міді цитрату в розведенні 1/20 при вмісті металів по 12,5 мкг/мл. Штам Escherichia coli ATCC 25922 був чутливим до досліджуваної композиції у розведенні 1/50, що відповідає вмісту металів срібла й міді по 5 мкг/мл. Встановили, що досліджувані розчини виявляють антимікробну дію як до грампозитивних, так і грамнегативних мікроорганізмів. Це свідчить про перспективність використання сполук срібла та міді у складі антимікробних препаратів м’якої та рідкої форми випуску. Быстрое формирование устойчивости микроорганизмов к антибиотикам вызывает необходимость поиска новых, альтернативных антимикробных лекарственных средств. С целью фармацевтической разработки препаратов изучена антимикробная активность различных концентраций растворов цитрата серебра и меди стандартным методом серийных разведений на тест-штаммах микроорганизмов. Наиболее чувствительным к раствору цитрата серебра оказался штамм Escherichia coli ATCC 25922 (F-50) и Pseudomonas aeruginosae АТСС 9027 при концентрации серебра в растворе 10 мкг/мл. Чувствительность Staphylococcus aureus 6538 Р проявилась в концентрации серебра 25 мкг/ мл. Полученные в ходе эксперимента данные указывают на то, что минимальная ингибирующая концентрация цитрата серебра (содержание серебра 500 мкг/мл) по отношению к тест-штамму Staphylococcus aureus 6538 Р составляет 20 мкг/мл, по отношению к Escherichia coli ATCC 25922 – 6,7 мкг/мл, а к Pseudomonas aeruginosae АТСС 9027 –10 мкг/мл соответственно. Staphylococcus aureus является чувствительным к раствору серебра и меди цитрата в разведении 1/20 при содержании металлов по 12,5 мкг/мл. Штамм Escherichia coli ATCC 25922 был чувствительным к исследуемой композиции в разведении 1/50, что соответствует содержанию металлов серебра и меди по 5 мкг/мл. Установлено, что исследуемые растворы проявляют выраженное антимикробное действие по отношению к грамположительным и грамотрицательным микроорганизмам. Это свидетельствует о перспективности использования соединений серебра и меди в составе антимикробных препаратов мягкой и жидкой формы выпуска. The fast formation of microbial resistance to antibiotics creates necessity of search for new alternative antimicrobial drugs. Aim. To study the specific antimicrobial activity of silver citrate and copper citrate for the purpose of pharmaceutical drugs developing. Methods and results. The antimicrobial activity of silver and copper citrate was studied using the standard method of serial dilutions in culture medium at different test strains of microorganisms. Results. The most sensitive to the silver citrate solution were the strain of Escherichia coli ATCC 25922 (F-50) and Pseudomonas aeruginosae ATCC 9027 at concentration 10 mcg/ml of silver in solution. Sensitivity of Staphylococcus aureus was detected at a concentration of 25 mcg/ml. The results obtained in the experiment indicated that the minimum inhibitory concentration of silver citrate (silver content of 500 mcg/ml) to the test strain of Staphylococcus aureus is 20 mcg/ml, relative to Escherichia coli ATCC 25922 - 6.7 mcg/ml, and a Pseudomonas aeruginosae ATCC 9027 -10 mcg/ml respectively. Staphylococcus aureus is sensitive to solution of silver and copper citrate at 1/20 dilution with content of metal 12.5 mcg/ml. The strain of Escherichia coli ATCC 25922 was sensitive to the test composition at 1/50dilution, which corresponds to the content of metals (silver and copper) - 5 mcg/ml. Conclusions. Researched solutions demonstrated antimicrobial activity against gram-positive and gram-negative microorganisms. The dependence of the antimicrobial action of the exposure time has been found. These researches give the opportunity to choose the dose of the active pharmaceutical ingredient in the composition of antimicrobial liquid and semi-solid dosage forms.
Исследование антимикробной активности цитратов серебра и меди с целью разработки фармацевтических препаратов
Investigation of antimicrobial activity of silver and copper citrate for the development of pharmaceuticals preparations
Keywords: антимікробні засоби; срібло; мідь; цитрати; антимикробные средства; серебро; медь; цитраты; Anti Bacterial Agents; Silver; Copper; Citrates